STRATEGI PT KERETA API INDONESIA UNTUK MENGHADAPI DAMPAK PERANG TARIF MURAH DI MASKAPAI PENERBANGAN INDONESIA - Wardiningsih, Suprihatmi Sri (JURNAL EKONOMI DAN KEWIRAUSAHAAN, 2009)
ABSTRACT Industrial deregulation of Indonesia air transport, bringing ugly impact to train industry in Indonesia. Decision of Government which derestricted boundary price under, making plane ticket price is progressively reached by broader society circle. Effect of ticket price difference between executive class train and plane do not too far, they which during the time use train as a means of more opting especial transportation move to plane. According To PT Kereta Api Indonesia (KAI) represent serious threat, especially for the route of long distance, but that way for the route of short distance do not too affect. Even some route there are tendency there is increase is amount of passenger Taken by strategy is KAI to face industrial emulation of air transport there are some step that is: Ticket price based on day, Zone system, Ticketing in internet, Make-Up of service and most important is short distance route concentration Keywords: Train Indonesia, strategy train short distance route.